Translating Proverbs in the Mate ras Mate Film Texts from Karonese Language into English - Milisi Sembiring; Vivi Novalia Sitinjak (Bina Nusantara University, 2019)
The research aimed to explore the problems and the solutions in translating proverbs in the SL into the TL. This research applied a qualitative research and supported by cultural and translation analyses. The data were collected from the dialogues of Ngapul and Yerti in the film of “Mate ras Mate”. The Karonese proverbs in the MRM film texts were the source language (SL). The researchers translated the SL and found out their equivalents in the target language (TL) in English. The data for this research were gathered from its film text. After collecting the proverbs in film, the researchers identified and translated them into English. The researchers applied the translation procedures of cultural equivalent, paraphrase, descriptive equivalent, and literal translation method to translate the proverbs in the SL into the TL. The result shows that many Karonese proverbs and cultural terms in the SL have no equivalent in the TL.